Analisis Pesan Dakwah Dalam Pernikahan Adat Masyarakat: Studi Pada Kampung Ema, Kabupaten Tambrauw - Yenjau, Syamsiyah; Sulaiman, Umar; Sari, Fatma (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2021)
This study aims to determine the message of da'wah contained in the marriage tradition of the Ema village community, Tambrauw Regency. To find out, the method used is the method of observation and interviews. This data is then processed and interpreted in the form of concepts that can support the object of discussion. This study's results indicate what is contained in the marriage of the abun tribe in Ema village, Tambrauw Regency. Furthermore, the message of da'wah contained and implied in the implementation of the marriage procession of the Abun Ema village tribe is as follows: Message of Aqedah Da'wah, Koba-Koba, and Payment of Milk, Sharia Da'wah Message, Mesok (Promise), Delivery of Dowry and Cloth and Money, Message of Moral Da'wah, Mesok (Proposal and Koba-Koba (Mat)